A low-cost and customizable alternative for commercial implantable cannula for intracerebral administration in mice. (October 2020) - Kazanskaya, Rogneda B.; Lopachev, Alexander V.; Fedorova, Tatiana N.; Gainetdinov, Raul R.; Volnova, Anna B.
Graphical abstract: Abstract: Stereotaxic intracerebral cannula implantation for neuroactive agent administration is a wide-spread method for chronic experiments requiring bypassing the blood-brain barrier in rodents. However, commercially available cannula are bulky and may interfere with animal movement or lead to their dislodging during grooming. As the number of cannula needed in one experiment, and the accompanying costs can be high, it is in the interest of researchers to produce them on their own. Custom cannula manufacturing also offers the flexibility of different cannula lengths, which is required for agent delivery to various brain structures. In this article we present a protocol for making guide cannula along with the accompanying systems required for injection, which are small, cost-effective, light, easy to make, reusable, and can be made from easily procured materials.